Classical Cardiovascular Risk Factors and HIV are Associated With Carotid Intima‐Media Thickness in Adults From Sub‐Saharan Africa: Findings From H3Africa AWI‐Gen Study. Issue 14 (16th July 2019) - Nonterah, Engelbert A.; Boua, Palwende R.; Klipstein‐Grobusch, Kerstin; Asiki, Gershim; Micklesfield, Lisa K.; Agongo, Godfred; Ali, Stuart A.; Mashinya, Felistas; Sorgho, Herman; Nakanabo‐Diallo, Seydou; Debpuur, Cornelius; Kyobutungi, Catherine; et al.
Abstract : Background: Studies on the determinants of carotid intima‐media thickness (CIMT), a marker of sub‐clinical atherosclerosis, mostly come from white, Asian, and diasporan black populations. We present CIMT data from sub‐Saharan Africa, which is experiencing a rising burden of cardiovascular diseases and infectious diseases. Methods and Results: The H3 (Human Hereditary and Health) in Africa's AWI‐Gen (African‐Wits‐INDEPTH partnership for Genomic) study is a cross‐sectional study conducted in adults aged 40 to 60 years from Burkina Faso, Kenya, Ghana, and South Africa. Cardiovascular disease risk and ultrasonography of the CIMT of right and left common carotids were measured. Multivariable linear and mixed‐effect multilevel regression modeling was applied to determine factors related to CIMT. Data included 8872 adults (50.8% men), mean age of 50±6 years with age‐ and sex‐adjusted mean (±SE) CIMT of 640±123μm. Participants from Ghana and Burkina Faso had higher CIMT compared with other sites. Age (β = 6.77, 95%CI [6.34–7.19]), body mass index (17.6[12.5–22.8]), systolic blood pressure (7.52[6.21–8.83]), low‐density lipoprotein cholesterol (5.08[2.10–8.06]) and men (10.3[4.75– 15.9]) were associated with higher CIMT. Smoking was associated with higher CIMT in men. High‐density lipoprotein cholesterol (−12.2 [−17.9– −6.41]), alcohol consumption (–13.5 [−19.1–−7.91]) and HIV (−8.86 [−15.7–−2.03]) were inversely associated with CIMT. Conclusions: Given the rising prevalence of cardiovascular diseases risk factors in sub‐Saharan Africa, atherosclerotic diseases may become a major pan‐African epidemic unless preventive measures are taken particularly for prevention of hypertension, obesity, and smoking. HIV‐specific studies are needed to fully understand the association between HIV and CIMT in sub‐Saharan Africa.